DESIGNING A MOTION COMIC â€œPERJALANAN PECILâ€ FEATURING KEDIRIâ€™S SIGNATURE SAMBAL TUMPANG TO SHOWCASE THE CULINARY DELIGHTS OF KEDIRI - Handaru, Wuri Cahya; Hamida, Mayliana Wahyu (VOK@SINDO : Jurnal Ilmu-Ilmu Terapan dan Hasil Karya Nyata, 2024)
Abstract: Sambal tumpang is a Javanese specialty. In Central Java, sambal tumpang is quite famous in several areas such as Solo, Klaten, Salatiga, Sragen, Boyolali, and Wonogiri. In East Java, the most famous area with sambal tumpang is Kediri. This research aims to introduce Kediri sambal tumpang as a typical food of Kediri City. This is because there are similarities in the use of sambal tumpang as a specialty food from other regions in Central Java. Based on observations made in the pecel tumpang Pudakit area Jl. Dhoho Kediri, it is known that teenagers with an age range of 15 - 20 years still have little interest in this typical Kediri sambal tumpang. Therefore, the target audience of the motion comic design "Pecil's Journey" will be intended for teenagers with that age range because of the lack of interest in Kediri's sambal tumpang. Motion comic is chosen because the media presents a way to enjoy comics with the latest presentation, namely with simple moving image animation. This was chosen in accordance with the general problem that exists, namely the lack of interest in reading among Indonesian people, especially today's generation of teenagers. The research method used in this design is qualitative. The qualitative method was chosen because the design of motion comics requires information data from trusted people as experts or accurate informants (key persons). The data collection methods used in this research are observation, interview, and literature study. The design objective of this Final Project is to produce a motion comic "Perjalanan Pecil" about sambal tumpang typical of Kediri to introduce the culinary of Kediri City.